2023
DOI: 10.1039/d3gc00489a
|View full text |Cite
|
Sign up to set email alerts
|

Green materials with promising applications: cyclodextrin-based deep eutectic supramolecular polymers

Abstract: Supramolecular polymers (SPs) based on macrocyclic host molecules as copolymer monomers are considered a promising class of advanced functional materials due to their satisfactory tunable properties and unique host-guest interactions....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 103 publications
(200 reference statements)
0
7
0
Order By: Relevance
“…The PDES increased the adsorption sites of OVA and enhanced multiple interactions between the sorbent and OVA. 211,212 Li et al 213 reported the modification of magnetic titanium dioxide nanoparticles using a deep eutectic solvent consisting of choline chloride (ChCl) and xylitol (Xyl) (Fe 3 O 4 @TiO 2 @[ChCl] [Xyl]) and its application to chymotrypsin (Chy) solid phase extraction (MSPE). There was also a group led by Ni et al 214 who used carbon nanotubes (CNTs) for magnetization and radical polymerization, followed by solid-phase extraction of bovine serum proteins (BSA) using 3-acrylamidopropyltrimethylammonium chloride solution (APTMAC) and xylitol (Xyl) to coat the surface (Fig.…”
Section: As a Functionalization Agentmentioning
confidence: 99%
“…The PDES increased the adsorption sites of OVA and enhanced multiple interactions between the sorbent and OVA. 211,212 Li et al 213 reported the modification of magnetic titanium dioxide nanoparticles using a deep eutectic solvent consisting of choline chloride (ChCl) and xylitol (Xyl) (Fe 3 O 4 @TiO 2 @[ChCl] [Xyl]) and its application to chymotrypsin (Chy) solid phase extraction (MSPE). There was also a group led by Ni et al 214 who used carbon nanotubes (CNTs) for magnetization and radical polymerization, followed by solid-phase extraction of bovine serum proteins (BSA) using 3-acrylamidopropyltrimethylammonium chloride solution (APTMAC) and xylitol (Xyl) to coat the surface (Fig.…”
Section: As a Functionalization Agentmentioning
confidence: 99%
“…For possible application as biomaterials, supramolecular polymers have to possess high stability and solubility in water. 8–10 For this purpose, the host–guest inclusion of macrocyclic hosts, such as cyclodextrins, 11–13 cucurbiturils 14–18 and pillararenes, 19,20 for hydrophobic monomeric or dimeric guests has been developed to allow for the formation of various crosslinked supramolecular polymers in aqueous solution. A more straightforward strategy for synthesizing water-soluble supramolecular polymers involves the use of multiple ionic interactions as driving forces.…”
Section: Introductionmentioning
confidence: 99%
“…[3] As highlighted in previous studies, [4][5] the advantages of DES include biodegradability, tunable physicochemical properties and ease of synthesis. The judicious selection of HBDs also allows DES with diverse characteristics and tailoring DES for specific applications such as extraction, [6][7] gas purification, [8] metal processing, [9] polymer synthesis, [10] biocatalysis [11] and electrochemistry. [12] Energy efficiency is also emphasized in the sixth principle of Green Chemistry.…”
Section: Introductionmentioning
confidence: 99%